(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the main factors for developing reflective culture among medical higher education students. Modern medical practice requires doctors not only to have deep theoretical knowledge, but also the ability to continuously reflect on their practice, analyze mistakes and strive for continuous self-improvement. The study analyzes the essence of reflective culture, its place in medical education and pedagogical factors influencing its development. The article is intended for specialists in the field of medical education, teachers and researchers.